Efektivitas Pendampingan dalam Meningkatkan Jangkauan Pasar dan Penjualan UMKM Thrifting Queenfau.outif melalui Media Sosial - Intan Novitasari Sah; Festi Syahputri L.; Laily Muzdalifah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The thrifting business in Indonesia has experienced significant growth in recent years, as it is increasingly in demand by the Indonesian people, especially from the middle to lower class youth, both women and men. Women's clothing thrifting MSMEs are also increasingly popular due to fashion trends that prioritize fashionable styles and affordable prices. Assisting thrifting MSMEs in optimizing digital marketing has become the right strategy to increase market reach and sales volume. Platforms such as TikTok have become the main channel utilized by thrifting MSMEs to market their products. The method used in this assistance is a qualitative method. This method uses a descriptive data collection process in the form of data from observations or interviews grouped in the form of documents and field notes during the mentoring process. The results show that a specially designed mentoring program can help thrifting MSMEs overcome challenges such as a lack of understanding of effective content strategies to increase sales. Through proper mentoring, thrifting MSMEs can increase visibility, engagement, and ultimately increase sales of Queenfau.outfit products significantly.